Quantitative comparison of human myocardial fiber orientations derived from DTI and polarized light imaging. (23rd October 2018) - Yang, Feng; Zhu, Yue-Min; Michalowicz, Gabrielle; Jouk, Pierre-Simon; Fanton, Laurent; Viallon, Magalie; Clarysse, Patrick; Croisille, Pierre; Usson, Yves
Abstract: Diffusion tensor imaging (DTI) is a non-invasive technique used to obtain the 3D fiber structure of whole human hearts, for both in vivo and ex vivo cases. However, by essence, DTI does not measure directly the orientations of myocardial fibers. In contrast, polarized light imaging (PLI) allows for physical measurements of fiber orientations, but only for ex vivo case. This work aims at quantitatively comparing the myocardial fiber orientations of whole human hearts obtained from cardiac DTI with those measured by PLI. Whole human neonatal and infant hearts were first imaged using DTI. The same whole hearts were then imaged using PLI. After DTI and PLI data are registered, the orientations of fibers from the two imaging modalities were finally quantitatively compared. The results show that DTI and PLI have similar variation patterns of elevation and azimuth angles, with some differences in transmural elevation angle range. DTI itself induces an underestimation of the range of transmural elevation angles by a factor of about 25° at the basal and equatorial slices and the reduction of spatial resolution further decreases this range. PLI data exhibit a 15°  ±  5° ( P   <  0.01) narrower transmural elevation angle range at apical slices than in basal or equatorial slices. This phenomenon is not observed in DTI data. In both modalities, the azimuth angle maps exhibit curved or twisting boundaries at the basal and apical slices. The experimental results globally enforce DTI as a valid imaging technique to reasonably characterize fiber orientations of the human heart noninvasively.